Proposing a new product creativity assessment tool and a novel methodology to investigate the effects of different types of product functionality on the underlying structure of factor analysis - Hazeri,K; Childs,PRN; Cropley,D (Design Society, 2017)
The aim of study is to indicate a gap in creativity research arising from products with dissimilar capabilities requiring independent creativity indicators that are empirically formed according to their functionality. Initially, a hypothesis for a criterion-based tool comprising 9 criteria and 40 indicators is put forward for assessing functional products. Then, a novel experimental approach is presented to indicate this variation. The first experiment uses the Consensual Assessment Technique (CAT) to measure the product creativity as well as the relationship between creativity and the criteria proposed. Then, EFA is considered to extract the irrelevant items and provide the optimum underlying structures for the factors used in each assessment. The validity of the models will then be investigated using the comparison of the goodness of fit indices between the estimated factor loadings calculated by CFA measurement and the empirical data collected from the second study. It is anticipated that the findings of this experiment will result in three dissimilar tools, where each comprised of specific indicators that appropriately established with respect to various product functionality.